Project-Based Learning and Developmentally Appropriate Practice in Geography Education: Enhancing Creative Thinking in Sustainable Resource Management - Anugrah Januar Ratri; Alfyananda Kurnia Putra; Yunita Permatasari; Putri Ayu Amalia (CV Bumi Spasial, 2025)
This study investigates the impact of integrating Project-Based Learning (PjBL) with Developmentally Appropriate Practice (DAP) as a complementary pedagogical framework on the creative thinking skills of senior secondary students studying sustainable natural resource management at SMA Negeri 1 Jombang, Indonesia. A quantitative quasi-experimental design employing a Pre-test Post-test Nonequivalent Control Group approach was conducted with 66 purposively selected grade XI students, divided into an experimental group receiving PjBL integrated with DAP and a control group receiving PjBL alone. The relatively small sample size may limit the statistical power to detect subtle effects. Data collection instruments comprised a validated essay test designed to measure multiple indicators of creative thinking, such as divergence, originality, fluency, elaboration, and convergent thinking, and structured classroom observations conducted by trained observers to assess student engagement and participation during the learning activities. The results of the Independent Sample T-Test analysis showed no significant difference between the two groups (p=0.560), although the mean score of the experimental class was slightly higher (77 vs. 76.4). Two-Way ANOVA also confirmed no significant difference by gender (p=0.422). Findings suggest that factors such as the short duration of the intervention, a rigid project structure limiting student autonomy, and assessment instruments lacking integration of spatial and sustainability contexts may have constrained the development of students’ creative thinking, as supported by qualitative reflections and post-intervention observations. This study recommends modification of DAP with integration of geospatial analysis-based challenges and extension of project duration to increase the relevance of sustainability-based Geography learning.